Baicalin Protects Vascular Tight Junctions in Piglets During Glaesserella parasuis Infection - Liu, Yu; Li, Xiaoyi; Zhang, Zhaoran; Zhang, Jiacheng; Xu, Jianfeng; Qiu, Yinsheng; Ye, Chun; Fu, Shulin; Wu, Zhongyuan; Hu, Chien-An Andy (Frontiers in Veterinary Science, 2021)
Glaesserella parasuis (G. parasuis) can cause Glässer's disease and severely affect swine industry worldwide. This study is an attempt to address the issue of the capability of G. parasuis to damage the vascular barrier and the effects of baicalin on vascular tight junctions (TJ) in order to investigate the interactions between the pathogen and the porcine vascular endothelium. Piglets were challenged with G. parasuis and treated with or without baicalin. The expressions of vascular TJ genes were examined using RT-PCR. The distribution patterns of TJ proteins were detected by immunofluorescence. The involved signaling pathways were determined by Western blot assays on related proteins. G. parasuis can downregulate TJ expression and disrupt the distribution of TJ proteins. Baicalin can alleviate the downregulation of vascular TJ mRNA, maintain the distribution, and prevent the abnormalities of TJ. These results provide ample evidence that baicalin has the capacity to protect vascular TJ damaged by G. parasuis through inhibiting PKC and MLCK/MLC pathway activation. As a result, baicalin is a promising candidate for application as a natural agent for the prevention and control of G. parasuis infection.